Structural and optical properties of low dimensional lead halide perovskites - Gómez, Mayra Alexandra Padrón (2018)
The study of perovskites in last few years has grown exponentially and made then one of the trending topic in materials science. The lead-based family of perovskites are important for their multiple applications as strong photoluminescence, narrow emission line width, and high exciton binding energy. Hybrid organic-inorganic perovskites are being widely explored for their optoelectronic properties; few of these materials exhibit broadband emission under ultraviolet excitation. In this work, we were synthesized, using the slow evaporation method, five single crystals of lead halide perovskites, three of them are low dimensional hybrid lead perovskites (DMA)11Pb4Br19, (DMA)14RbPb4Br23 and (DMA)9S4Pb5Br27, all compounds exhibit a novel crystal structure. Additionally, we discuss the behavior of CsPb2Br4.3I0.7 and Cs4PbBr6, also low dimensional compounds, under high pressure investigated using Raman and photoluminescence techniques. Several structural phase transitions were identified on this compounds.